Digital Learning Characteristics and Principles of Information Resources Knowledge Structuring - Belichenko, Margarita; Davidovitch, Nitza; Kravchenko, Yuri (European journal of educational research, 2017)
Analysis of principles knowledge representation in information systems led to the necessity of improving the structuring knowledge. It is caused by the development of software component and new possibilities of information technologies. The article combines methodological aspects of structuring knowledge and effective usage of information resources which are designed for the scientific and methodological study of practical recommendations in Digital learning implementation. It is shown at the paper that one of the most important problems, which face the processing of knowledge or construction systems, is knowledge representation. The main idea of the paper is increasing the efficiency at the university learning process on the basis of a possible applications and rational structuring knowledge. The proposed concept of using information resources of Digital Learning is based on the idea of using the principles of abstraction, encapsulation, modularity, hierarchy, typing, concurrency preservation and implementation in such stages of this process as algorithmic support of knowledge structuring and structured transfer of knowledge to students. The topic of the article is unique as we try to see Digital learning in multidisciplinary aspects: education, mathematics, statistics. The article combines a theoretical approach to structuring knowledge that is based on the integrated usage of fuzzy semantic network, theory of predicates, Boolean functions, theory of complexity of network structures and practical aspects and ways of construction Digital Learning Systems at the University.